Fruit and vegetable consumption and mental health across adolescence: evidence from a diverse urban British cohort study - Peiyuan Huang; Majella O'Keeffe; Christelle Elia; Alexis Karamanos; Louise M. Goff; Maria Maynard; J. Kennedy Cruickshank; Seeromanie Harding (BMC, 2019)
Abstract Background Evidence on the relationship between fruit and vegetable consumption (FV) and mental health in adolescence is sparse and inconsistent. Social determinants of FV include ethnicity, family environments and economic disadvantage. We investigated the relationship between FV and mental health in the British multi-ethnic Determinants of Adolescents (now young Adult) Social well-being and Health (DASH) longitudinal study. Methods A longitudinal study of 4683 adolescents living in London at age 11-13 years and followed up at 14-16 years. FV was measured using validated questions on the number of portions consumed daily. Mental health was measured by the Strengths and Difficulties Questionnaire as mean Total Difficulties Score (TDS) and by classification as a 'probable clinical case' (TDS > 17). Social measures included ethnicity, parenting and socioeconomic circumstances. Multilevel modelling was used to investigate the association between FV and mental health throughout adolescence. Results Low FV was common among adolescents, with approximately 60-70% of adolescents reporting < 5 portions/day and 20-30% reporting < 1 portion/day. In late adolescence, most ethnic minority groups reported lower FV than their White peers. In fully adjusted models, < 1 portion/day remained a significant correlate with mean TDS (Coef: 0.55, 0.29-0.81, P < 0.001) and TDS > 17 (Odds Ratio: 1.43, 1.11-1.85, P = 0.007). Gender- or ethnic-specific effects were not observed. Low parental care partly attenuated the association between FV and mental health. Conclusions Low FV is a longitudinal correlate of poor mental health across adolescence. A focus on FV in parenting interventions could yield interrelated benefits across developmental outcomes given its importance to both physical and socioemotional health.